Brachial Plexus Birth Injury: Trends in Early Surgical Intervention over the Last Three Decades. Issue 5 (23rd May 2022) - Wells, Matthew E.; Tihista, Mikel C.; Diamond, Shawn
Abstract : Background: Early surgical management of brachial plexus birth injury has advanced owing to targeted surgical techniques and increases in specialty-centers and multi-institutional collaboration. This study seeks to determine trends in the early surgical management of BPBI over the last 30 years. Methods: A systematic review was performed through MEDLINE (PubMed) identifying studies limited to the early surgical management of BPBI from 1990 to current. Patients treated after 1 year of age (ie, tendon transfers and secondary reconstructive efforts) were excluded. Diagnostic tests, age of intervention, surgical treatment modalities, and outcome scoring systems were extrapolated and compared so as to determine trends in management over time. Results: Seventeen studies met criteria, summating a total of 883 patients. The most commonly reported physical examination classifications were the Mallet and AMS scoring systems. Most patients underwent neuroma excision and sural nerve autografting (n = 618, 70%) when compared with primary nerve transfers (148, 16.8%), primary nerve transfer with autografting combinations (59, 6.7%), or neurolysis alone (58, 6.6%). There was no significant change in the proportion of patients treated with sural nerve grafting, combination graft and transfer procedures, or isolated neurolysis over time. However, there has been a significant increase in the proportion of patients treated with primary nerve transfer procedures ( τ b = 0.668, P < 0.01) over time. Conclusion: Although neuroma excision and sural nerve autografting has been the historic gold-standard treatment for brachial plexus birth injury, peripheral nerve transfers have become increasingly utilized for surgical management.